Uma proposta de redução de perdas no setor hortifruti de uma frutaria - Dezingrini, Ricardo (2018)
Due to the great waste of fruits and vegetables in the day-to-day routine of the fruit shop, an analysis was carried out precisely in the waste of the fruit and vegetable branch, to propose a system to reduce it. With the proper knowledge on the subject and on what causes waste, the collaborators were also motivated to give their contributions, and later trained to carry out the handling and storage activities in the correct way. With the collection, it was possible to establish percentage values for waste. Daily and weekly data on the supply of products from regional distributors and CEASA were also compared. As a result, it appears that the most important activity in this field is the purchase of fruit. The quality of the products, at the time of purchase, has to be the best possible, bringing a prolonged useful life and considerably reducing waste.